Triple targeting of mutant EGFRL858R/T790M, COX-2, and 15-LOX: design and synthesis of novel quinazolinone tethered phenyl urea derivatives for anti-inflammatory and anticancer evaluation - Hend Kothayer; Samar Rezq; Ahmed S. Abdelkhalek; Damian G. Romero; Samar S. Elbaramawi (Taylor & Francis Group, 2023)
We designed and synthesised novel quinazolinone tethered phenyl urea derivatives (6a-p) that triple target the double mutant EGFRL858R/T790M, COX-2, and 15-LOX. Compounds (6e, 6d, 6j, 6m, and 6n) not only had low micromolar IC50 inhibitory activities against the three targets, but they also showed good selectivity for COX-2 over COX-1 and for EGFRL858R/T790M over wild-type EGFR. Except for 6e and 6n, all of the tested compounds inhibited the NO production significantly more potently than celecoxib, diclofenac, and indomethacin. Compounds 6i and 6k reduced ROS levels more effectively than celecoxib and diclofenac. In terms of inhibiting TNF-α production, 6o-treated cells showed TNF-α level, which is ∼10 times lower than celecoxib. Furthermore, 6e and 6j had the highest anticancer activity against the breast cancer cell line BT-459 with growth inhibition percentages of 67.14 and 70.07%, respectively. Docking studies confirm their favoured binding affinity. The proposed compounds could be promising multi-targeted leads.